Galaxy clusters, voids and elliptical galaxies using the ROSAT PSPC - Carr, Michael (Trinity College (Dublin, Ireland). School of Physics, 2003)
The ROSAT data archive contains of the order of 100,000 sources observed by the ROSAT PSPC (Position Sensitive Proportional Counter). For many sources detected with the ROSAT PSPC there is not a sufficient number of photons ( ~ 1,000) to make reliable spectra. As an alternative to spectra, Hardness Ratios (HR's)(ratios of photons in selected bands of the spectra) are calculated. It is not possible to determine spectral parameters directly from HR's.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin